Cyberbullying Victimization and Non-suicidal Self-Injurious Behavior Among Chinese Adolescents: School Engagement as a Mediator and Sensation Seeking as a Moderator - Yu, Chengfu; Xie, Qi; Lin, Shanyan; Liang, Yue; Wang, Guodong; Nie, Yangang; Wang, Jianping; Longobardi, Claudio (Frontiers in Psychology, 2020)
Although a large body of research has indicated that cyberbullying is a crucial risk factor for adolescent non-suicidal self-injury (NSSI) behavior, the mediating and moderating mechanisms underlying this relationship remain unclear. To address this research gap, this study, based on the social control theory and the organism-environment interaction model, was designed to test whether school engagement mediated the relationship between cyberbullying and adolescent NSSI and whether this mediating effect was moderated by sensation seeking. A sample of 1102 adolescents (Mage = 13.17; SD = 0.69) anonymously completed the questionnaires. The results showed that the positive association between cyberbullying and adolescent NSSI was mediated by school engagement. Moreover, this indirect link was significant for adolescents with high-level sensation seeking but nonsignificant for adolescents with low-level sensation seeking. These findings highlight school engagement as a potential mechanism linking cyberbullying to adolescent NSSI, and high sensation seeking was an important risk factor to amplify this indirect effect. Intervention programs aimed at reducing NSSI among adolescents may benefit from the current research.